THE SECOND CONGRESS OF URAL PEDIATRICIANS WITH INTERNATIONAL PARTICIPATION «RELEVANT PEDIATRIC PROBLEMS» AND THE FIRST URAL FORUM OF CHILDREN'S NURSES - Article Editor (Union of pediatricians of Russia, 2012)
.